HAK KEBEBASAN BERPENDAPAT DI ERA DIGITAL DALAM PERSPEKTIF HAK ASASI MANUSIA - Andriansyah, Muhammad Wahyu; Kusnadi, Sekaring Ayumeida (Gorontalo Law Review, 2024)
Freedom of expression is a fundamental human right in a democratic society that allows citizens to voice opinions, participate in public discussions, and criticize the government without fear. This article explores the legal basis for freedom of expression in Indonesia and analyzes the fulfillment of this right from a human rights perspective. The focus of the article also covers the challenges and opportunities that arise in the ever-evolving digital era, recognizing its role in maintaining social and political justice. In the context of human rights, freedom of expression is recognized as a fundamental right, but it needs to be balanced with legal and ethical responsibilities in the use of digital technology. This research reviews regulations such as the 1945 Constitution, the Criminal Code, the Human Rights Law, and the ITE Law relating to freedom of expression and looks for solutions to create a democratic digital environment without sacrificing human rights.